Isu Terorisme dan Stigmatisasi Terhadap Pondok Pesantren (Meluruskan Kesalahpahaman terhadap Pondok Pesantren - Amir Mu`allim (Millah: Journal of Religious Studies, 2006)
The terrorism issue has very popular in the beginning of 3th millennium, especialy after 9th September 2001 tragedy. After this tragedy, western states, especially USA accused every Islamic institution as terrorist in the world This stigma is also directed to pondok pesantren as one of Islamic education institution in Indonesia. It is caused by two factors, first, there were some terrorists have studied in pondok pesantren and second, there subject of jihad in pondok pesantren. But their action is not pondok pesantren teaching. Pondok pesantren curriculum does not teach terror, because pesantren is the place for Islamic generation to learn about religion. Islamic values, akhlakul karimah to form them to be virtuous generation, both for them self and for society. Terror which done by person from pesantren is as reaction for western terror and attacking to many moslim countries i.e. Afghanistan, Iraq, Palestine, Chechnya, etc